GEOCHEMISTRY AND RECONSTRUCTION OF THE PROTOLITH COMPOSITION OF THE BASEMENT OF THE PECHENGA PALEORIFT - Vetrin V.R.; Delenitsyn A.A.; Turkina O.M.; Ludden J. (My University, 2003)
The basement of the Early Proterozoic Pechenga paleorift was penetrated by the Kola Superdeep Borehole at depths from 6842-12261 m. The main types of basement rocks are gneisses of dacite-plagiorhyodacite (tonalite-trondhjemite) compositions associating with amphibolites, gneisses with aluminous minerals, and banded iron formation. The basement of the paleorift and near-surface rock associations of the northwestern part of the Kola-Norwegian block have identical ages, similar protolith compositions, and are the main types of the sedimentary-volcanic and plutonic rocks of the Late Archean granite-greenstone domain of the northwestern part of the Kola-Norwegian terrain, which was broken into isolated segments in the Paleoproterozoic. The Archean basement rocks of the paleorift are strongly altered by the processes of Proterozoic magmatism and metasomatism related to the formation of the Pechenga structure. In the Proterozoic, the Pechenga basement and its nearest framing were intensely affected by the emplacement of numerous mafic-ultramafic bodies, retrograde metamorphism under amphibolite and epidote-amphibolite facies conditions, granitization coeval with the metamorphism, and formation of postorogenic granitic dikes. For the majority of the Proterozoic processes, a connection was established with deep sources formed from the depleted mantle variably enriched in incompatible elements.
Keywords: Precambrian::Proterozoic; Докембрий::Протерозой